Conversations and Allusions - Spellman, Catherine (Actar D, 2021)
Enric Miralles (1955-2000) remains one of the most prominent architects of his generation. The significance of his architectural design lies in his seamless integration of site and building and his use of space to serve the everyday conditions of life. Practicing for less than twenty-five years Miralles designed over 150 projects, many are now built: the Scottish Parliament Buildings, Santa Caterina Market, Vigo University, Diagonal Mar Park, Alicante Gymnastic Center, and Igualada Cemetry. This book brings together previously unpublished essays and lectures by his former collaborators and friends. Each contributor in this timely publication offers insight on Miralles' practice of architecture as a way of creating positive change in the world.